2014
DOI: 10.1002/jcla.21733
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Chemiluminescent Immunoassay for Serum GPC3 and Simultaneous Measurements Alone With AFP and CK19 in Diagnosis of Hepatocellular Carcinoma

Abstract: An applicable chemiluminescent immunoassay with stable performance against GPC3 in diagnosing HCC has been established and the combination of GPC3 with CK19 and AFP could improve the diagnostic sensitivity for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 26 publications
1
45
1
Order By: Relevance
“…However, because the mainstream products of chemiluminescent reagents and instruments use proprietary technologies, these platforms are not conducive to the common alterations and development within the scientific community. With the support of the National High Technology Research and Development Program of China, an open chemiluminescence analysis platform has been developed for diagnostic reagents development . Our previous work has confirmed that HE4 plays a crucial role in tumor formation and growth in ovarian cancer cells and may be a potential therapeutic target for epithelial ovarian cancer .…”
Section: Introductionmentioning
confidence: 88%
“…However, because the mainstream products of chemiluminescent reagents and instruments use proprietary technologies, these platforms are not conducive to the common alterations and development within the scientific community. With the support of the National High Technology Research and Development Program of China, an open chemiluminescence analysis platform has been developed for diagnostic reagents development . Our previous work has confirmed that HE4 plays a crucial role in tumor formation and growth in ovarian cancer cells and may be a potential therapeutic target for epithelial ovarian cancer .…”
Section: Introductionmentioning
confidence: 88%
“…It may be because the different antibody epitopes used in these methods [16,17], which may capture several forms of secreted GPC3 [9,18,19], such as the fulllength glycated form of GPC3 or a shorter forms of soluble GPC3. Distinct difference in sensitivity and specificity has also been reported [14][15][16]. In addition, these methods have some shortcomings, such as low sensitivity and narrow detection range of ELISA, the radiation and pollution of RIA, and higher cost of CLIA.…”
Section: Introductionmentioning
confidence: 92%
“…Several methods have been developed for the detection of serum GPC3, such as ELISA, competitive radioimmunoassay and chemiluminescent immunoassay, however, all these kits are still remained for research use only. The level of serum GPC3 ranges from 924.8 pg/mL to several hundreds of ng/mL in HCC patients using different methods [13,14]. Yasuda et al even found it didn't work well to diagnose HCC using a commercial ELISA kit with GPC3 antibody 1G12 [15].…”
Section: Introductionmentioning
confidence: 97%
“…The simultaneous detection of CK19 and GPC3 expression in HCC patients was shown to be a predictive indicator of higher risks of cancer invasion and metastasis, as well as worse treatment outcome 35. Furthermore, the combination of CK19 and GPC3 demonstrated better diagnostic sensitivity (90.6%) compared with the use of GP3 alone (54.2%) when applied for the detection of HCC in a study cohort of 518 patients 36. Consistently, several other studies also confirmed a correlation between increased CK19 expression and a lower survival rate and/or a shorter remission period in HCC patients 37,38.…”
Section: Review-biomarkers In Hccsmentioning
confidence: 99%